Consumer acceptance of processed telang BUTERI flower and BUSER KING coffee products - Saati, Elfi Anis; Purwati, Titik; Prayitno, Trio Ageng; Argarini, Dian Fitri; Mistianah, Mistianah; Ambarawati, Mika; Budiono, Dwi; Herlambang, Alexander (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2024)
Processed telang flower and coffee products from Malang must be introduced to the public as typical Malang food tourism, such as processed telang BUTERI flower and BUSER KING coffee products. The purpose of the study was to determine consumer acceptance of processed telang BUTERI flower and BUSER KING coffee products through organoleptic tests. The type of research is quantitative descriptive research with organoleptic test methods through hedonic tests (likeability). The research sample was 40 researchers for processed telang BUTERI flower products and 50 panelists for processed BUSER KING coffee products. The research instrument was a hedonic test sheet with a scale of 1 to 5 (taste, aroma, appearance, texture, and overall). The research data are quantitative data of the percentage of preference and qualitative data in the form of information or panelist comments. The data analysis technique is quantitative descriptive. The results of the study indicate that consumer acceptance of processed telang BUTERI flower products from the taste aspect is 60.5%, aroma aspect is 61%, appearance aspect is 70%, texture aspect is 63.5%, and overall aspect is 67%. Meanwhile, consumer acceptance of processed BUSER KING coffee products from the taste aspect is 74.4%, aroma aspect is 79.6%, appearance aspect is 74.8%, texture aspect is 74.8%, and overall aspect is 82.4%. The study concludes that processed telang BUTERI flower and BUSER KING coffee products can be accepted by consumers. The public can consume telang BUTERI flower and BUSER KING coffee processed products because they have halal certificates, NIB, and PIRT certificates.